Advanced intestinal regulation improves bowel preparation quality in patients with constipation: A systematic review and network meta-analysis - Ding, Liang; Duan, JinNan; Yang, Tao; Jin, ChaoQiong; Luo, Jun; Ma, Ahuo (Frontiers in Pharmacology, 2023)
Background: Inadequate bowel preparation（IBP）has a critical influence on colonoscopy procedure and associated with significantly lower rates of detection of colorectal lesions. Constipation is an important risk factor of IBP and some studies have attempted to address the bowel cleansing for constipated patients. However, there still lack consensus to guide the clinical work of bowel preparation (BP) for patients with constipation. Therefore, we aimed to perform a network meta-analysis to compare the overall efficacy of various regimens for BP in constipated patients. Methods: We performed a comprehensive search of Pubmed, MEDLINE, EMBASE, Cochrane, and Web of science to identify randomized controlled trials (RCTs) of BP regimens in constipated patients, update to January 2021. Two investigators independently evaluated articles and extracted data. The odds ratio (OR) with a 95 % confidence interval (CI) was used to combine dichotomous data of primary outcome which was defined as adequate bowel preparation (ABP). Rank probability was used to exhibit the outcome of network meta-analysis. Results: Eleven studies included 1891 constipated patients were identified as suitable for inclusion. The proportion of ABP was associated with the administration of intensive regimen (OR 2.19, 95 % CI 1.16 to 4.17, P=0.02, I2 =84 %). Moreover, intensive regimen had a significantly efficacy and light heterogeneity when use same basic laxative program (OR 4.06, 95 % CI 3.04 to 5.43, P＜0.0001, I2 =0 %). In network meta-analysis, the protocol of NR+A (normal regimen plus advanced intestinal regulation) had a significant effect for BP compared with NR+IR (normal regimen plus irritating laxative regimen) (OR:5.21,95%CI 1.18 to 24.55), H PEG (4L- Polyethylene glycol ) (OR:8.70,95%CI 1.75 to 52.56) and NR (Normal Regimen) (OR:7.37,95%CI 2.33 to 26.39). In the rest protocols, no significant difference in any comparison. No significant severe adverse events (AEs) associated with BP was reported in included studies. Conclusions: Intensive regimens could improve bowel cleansing quality for patients with constipation and advanced intestinal regulation regimens may be superior to others.